Ethanol Stimulates Locomotion via a Gαs-Signaling Pathway in IL2 Neurons in Caenorhabditis elegans. Issue 3 (25th September 2017) - Johnson, James R; Edwards, Mark R; Davies, Huw; Newman, Daniel; Holden, Whitney; Jenkins, Rosalind E; Burgoyne, Robert D; Lucas, Robert J; Barclay, Jeff W
Abstract: Alcohol abuse is among the top causes of preventable death, generating considerable financial, health, and societal burdens. Paradoxically, alcohol... Alcohol is a potent pharmacological agent when consumed acutely at sufficient quantities and repeated overuse can lead to addiction and deleterious effects on health. Alcohol is thought to modulate neuronal function through low-affinity interactions with proteins, in particular with membrane channels and receptors. Paradoxically, alcohol acts as both a stimulant and a sedative. The exact molecular mechanisms for the acute effects of ethanol on neurons, as either a stimulant or a sedative, however remain unclear. We investigated the role that the heat shock transcription factor HSF-1 played in determining a stimulatory phenotype of Caenorhabditis elegans in response to physiologically relevant concentrations of ethanol (17 mM; 0.1% v/v). Using genetic techniques, we demonstrate that either RNA interference of hsf-1 or use of an hsf-1 ( sy441 ) mutant lacked the enhancement of locomotion in response to acute ethanol exposure evident in wild-type animals. We identify that the requirement for HSF-1 in this phenotype was IL2 neuron-specific and required the downstream expression of the α-crystallin ortholog HSP-16.48 . Using a combination of pharmacology, optogenetics, and phenotypic analyses we determine that ethanol activates a Gαs -cAMP-protein kinase A signaling pathway in IL2 neurons to stimulate nematode locomotion. We further implicate the phosphorylation of a specific serine residue (Ser322) on the synaptic protein UNC-18 as an end point for the Gαs -dependent signaling pathway. These findings establish and characterize a distinct neurosensory cell signaling pathway that determines the stimulatory action of ethanol and identifies HSP-16.48 and HSF-1 as novel regulators of this pathway.